2022
DOI: 10.1590/1678-992x-2020-0235
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel composed of potassium acrylate, acrylamide, and mineral as soil conditioner under saline conditions

Abstract: Hydrogels have potential as soil conditioners due to their high capacity to retain water and mitigate soil salinity. However, investigations under saline conditions are necessary because there are losses in both water absorption and salinity mitigation depending on the composition of hydrogel and ions involved in salinity. In this work, we studied a commercial hydrogel in two experiments. The first experiment was conducted in the laboratory to evaluate the absorption by the hydrogel of water with electrical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…The use of hydrogel ensures moisture retention in the soil, increasing water availability for plants (Saha et al, 2020;Sousa et al, 2023;Edvan et al, 2023), being a promising strategy to be used in the production of plants of agronomic interest in arid regions, as it enhances the germination process and initial development of crops (Ai et al, 2020). In sandy textured soil under saline conditions, Costa et al (2022) found that the use of hydrogel polymer reduced water loss by 58%. In the production of Pinus pinea, El-Asmar et al (2017) observed that the hydrogel promoted increases of 25% in biomass, and, at the same time, prolonged the survival time of the seedlings.…”
Section: Introductionmentioning
confidence: 99%
“…The use of hydrogel ensures moisture retention in the soil, increasing water availability for plants (Saha et al, 2020;Sousa et al, 2023;Edvan et al, 2023), being a promising strategy to be used in the production of plants of agronomic interest in arid regions, as it enhances the germination process and initial development of crops (Ai et al, 2020). In sandy textured soil under saline conditions, Costa et al (2022) found that the use of hydrogel polymer reduced water loss by 58%. In the production of Pinus pinea, El-Asmar et al (2017) observed that the hydrogel promoted increases of 25% in biomass, and, at the same time, prolonged the survival time of the seedlings.…”
Section: Introductionmentioning
confidence: 99%
“…These unique materials are being used in several commercial applications, for example, as ophthalmic devices, biosensors, biological membranes, and drug carriers [ 1 , 2 ]. Potential applications of hydrogels as soil conditioners and as removal agents for heavy metal ions have also been mentioned in the literature [ 6 , 7 , 8 ]. The properties of hydrogels strongly depend on the synthesis, concentration, and nature of components and the polymerization process.…”
Section: Introductionmentioning
confidence: 99%